?KINETIC STUDIES ON THIOCYANATE SUBSTITUTION IN DIMERIC HALO SCHIFF BASE CHROMIUM (III) COMPLEXES -A CORRELATION OF RATES AND STRAIN ENERGIES (Biological Sciences - PJSIR, 1997)
The kinetics and mechanism of thiocyanate substitution in dimeric chromium (III) complexes, Cr2L2 'C12 and Cr2L2"C12where L' =C'SH,yNP2 (deprotonated Schiffbase derived from diethylenetriamine and salicylaldehyde) and L" = C2,H26NP2 (deprotonated Schiff base derived from N, N Bis (2-aminoethyl) I, 3 propanediamine and salicylaldehyde) have been studied spectrophotometricaIly al20°C in ammonium thiocyanate medium in the concen- tration range 0.2-1.0 mol dm=.Thc values of Ko,,",show anonlinear dependence on square ofNCS-concentration for both the complexes. These have been found to increase with the increase in derived strain energies of the metal-ligand rings in the complexes.